2012
DOI: 10.1161/circep.111.968677
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Catheter Ablation of Ventricular Tachycardia in Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy

Abstract: A rrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C) is an inherited cardiomyopathy characterized by progressive fibrofatty replacement of the right ventricular myocardium. Structural abnormalities can be diffuse 1 and provide a substrate for reentrant ventricular tachycardia (VT). Studies have shown a significantly high incidence of ventricular arrhythmias 2-4 among patients with ARVD/C. Although the risk of sudden death is mitigated by implantable cardioverterdefibrillator (ICD) implantation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(99 citation statements)
references
References 39 publications
2
91
1
5
Order By: Relevance
“…However, RFA can be considered as an adjuvant therapy to ICD placement in patients with VT or frequent ICD firing despite using BB or antiarrhythmic drugs or in patients who were not able to tolerate ARVC recommended medications (class I) [22]. Furthermore, multiple electrophysiologic mapping techniques have been used to treat VA including voltage mapping and substrate mapping [31,32,4648]. …”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…However, RFA can be considered as an adjuvant therapy to ICD placement in patients with VT or frequent ICD firing despite using BB or antiarrhythmic drugs or in patients who were not able to tolerate ARVC recommended medications (class I) [22]. Furthermore, multiple electrophysiologic mapping techniques have been used to treat VA including voltage mapping and substrate mapping [31,32,4648]. …”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…Modern studies providing long term follow-up on large number of patients, 37,38 reported very high recurrence rates after the first procedure despite a combined endo/epicardial approach, although the cumulative freedom from VT following procedures using 3D-EVM and/or epicardial approach was significantly greater than conventional ablation. The most likely reason is the progressive nature of the disease with modification of the arrhythmic substrate over time.…”
Section: Reviewmentioning
confidence: 99%
“…Although recent technological advances with electroanatomic and voltage mapping systems have significantly improved outcomes [27][28], catheter ablation can reduce the frequency of VT episodes, but long-term follow-up studies have demonstrated a risk of recurrence. However, only an endocardial approach was used in most of the cases previously reported [29][30][31].…”
Section: Arrhythmogenic Right Ventricular Cardiomyopathymentioning
confidence: 99%